ASPEK PERLINDUNGAN HUKUM ATAS DATA PRIBADI NASABAH PADA PENYELENGGARAAN LAYANAN INTERNET BANKING (Studi Kasus Pada PT. Bank Mandiri Cabang Baturaja) - Titie Syahnaz Natalia (KEADILAN PROGRESIF, 2019)
In this modern era, internet banking services have been widely used by banks inIndonesia. In particular, Bank Mandiri Baturaja Branch has also provided internet bankingservices for its customers. This service can make it easier for customers to make transactions,but this convenience is not always safe for these customers, because with this service many ofthe customers get losses and the customer's personal data can be hacked by hackers / cybercrime. The research question is how the legal aspects of banks in protecting customers'personal data on internet banking services and how the implementation of legal protection ofpersonal data of internet banking customers at PT Bank Mandiri Baturaja Branch By usingthe method of library (Library Research), field research (Field Research) and this researchuses narrative analysis using descriptive data. The results of the study found that the legalaspects of the bank in protecting customers using the internet banking PT. Bank MandiriBaturaja Branch in accordance with applicable law, but at this time the law that governsdirectly about internet banking does not yet exist, but it is associated with other regulations.